2016
DOI: 10.1111/jgs.14399
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the Management of Denture Stomatitis: A Systematic Review and Meta‐Analysis

Abstract: The results are supportive of the use of nystatin and disinfecting agents in the treatment of DS, but clinicians need to be aware that individual studies had high risk of bias and that the overall quality of the individual reports was judged to be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 45 publications
5
57
0
5
Order By: Relevance
“…14 Other factors that predispose oral candidiasis in immunocompetent patients are occlusion trauma, poor oral hygiene, xerostomia, and diabetes. 15,16 Some studies have reported increased virulence of Candida tropicalis in immunocompromised patients; [17][18][19] which is in agreement with the clinical findings of this case report regarding HIV status. It is important to order HIV testing in cases of candidiasis since its association with the virus is common.…”
Section: Discussionsupporting
confidence: 91%
“…14 Other factors that predispose oral candidiasis in immunocompetent patients are occlusion trauma, poor oral hygiene, xerostomia, and diabetes. 15,16 Some studies have reported increased virulence of Candida tropicalis in immunocompromised patients; [17][18][19] which is in agreement with the clinical findings of this case report regarding HIV status. It is important to order HIV testing in cases of candidiasis since its association with the virus is common.…”
Section: Discussionsupporting
confidence: 91%
“…The problems resulting from the accumulation of microorganisms are often addressed with medication . An alternative solution is the addition of antimicrobials to the prosthetic device.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 25% of individuals needing complete upper dentures also presented such lesion. Denture stomatitis is the most common oral mucosal lesion in community-dwelling elderly people and it is characterized by an inflammatory condition of the denture-bearing mucosa, mostly associated with Candida colonization 22 .…”
Section: Discussionmentioning
confidence: 99%